Protease inhibitors for the treatment of hepatitis C virus infection - de Leuw, Philipp (GMS Infect Dis, 2017)
The hepatitis C virus (HCV) has affected an estimate of 80 million individuals worldwide and is a strain of public health. Around 25–30% of patients in Europe and the US infected with HIV are coinfected with HCV. Despite treatment modalities containing a NS3/4A protease inhibitor in combination with pegylated interferon and ribavirin prior to 2013 improved SVR rates, the amount of severe side effects was high. Nowadays, oral direct-acting antivirals (DAAs) combination therapy offers excellent treatment efficacy, safety and tolerability. This review focuses on current literature and clinical evidence and their impact regarding NS3/4A protease inhibitors. In addition, pitfalls in treatment from HIV- and HBV-coinfected patients will also be discussed. In the era of DAA treatment, the third-generation pan-genotypic NS3/4A protease inhibitors (mainly grazoprevir, glecaprevir and voxilaprevir) show a high antiviral activity and genetic resistance barrier with cure rates of over 95% when combined with an NS5A inhibitor, irrespectively of baseline resistance associated variants (RASs) being present. These new key components of DAA combination therapy are impressive options to eradicate HCV in the so called difficult-to-treat population (e.g. compensated cirrhosis, end-stage renal disease and patients who failed previous DAA treatment).